The Effect of the Implementation of E-Crm Electronic Satisfaction and Loyalty, Electronic Consumers of Mellat Bank’s Website - Jamali, Mehdi; Mehrabadi, Mohammad Azimi; Pouri, Mohammad (Journal of History Culture and Art Research, 2017)
Organizations that compete for power in the market constantly looking for ways to overcome their rivals. Today’s customers want to engage with the organization. Successful customer relationship management is one of the major competitive advantages that organizations can use to prevent the transmission of clients to other organizations deemed of operation. The degree to which an organization is able to maintain effective communication with their clients, more opportunities to offer more services to its business customers will offer. Considering the above study to evaluate the effect of the implementation of E-CRM on e-satisfaction and customer loyalty has paid electronically, users of the Mellat Bank’s website. To collect information from the questionnaire with Cronbach’s alpha was used validation. Respondents were customers and users of online services of the Mellat Bank’s website. Survey research method - has been described. To analyze the data, descriptive and inferential statistical methods such as correlation analysis, Pearson and Spearman correlation coefficient and linear regression analysis using SPSS software is used. The results show that the implementation of E-CRM is a positive and significant impact on customer satisfaction and loyalty-mail.